2019
DOI: 10.1055/s-0039-3402424
|View full text |Cite
|
Sign up to set email alerts
|

Extensor Tendon Entrapment on Computed Tomography Imaging of Distal Radius Fractures

Abstract: Objective To examine the association between distal radius fractures and tendon entrapment identified on computed tomography (CT) imaging. Patients and Methods After Institutional Review Board approval, we retrospectively reviewed distal radius fractures that underwent CT imaging from an electronic database between January 2006 to February 2018 at a single level 1 hospital trauma center. We categorized all distal radial fractures according to the AO-OTA (AO Foundation/Orthopaedic Trauma Association) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In Galeazzi's fractures, the extensor carpi ulnaris tendon may also be involved 6 . Nigh retrospectively reviewed their cases and found a case with ECRL tendon entrapment in computed tomography; however, it was not noted in the operative report 1 . To the best of our knowledge, intraoperatively confirmed entrapment of radial wrist extensor tendons at the fracture site has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Galeazzi's fractures, the extensor carpi ulnaris tendon may also be involved 6 . Nigh retrospectively reviewed their cases and found a case with ECRL tendon entrapment in computed tomography; however, it was not noted in the operative report 1 . To the best of our knowledge, intraoperatively confirmed entrapment of radial wrist extensor tendons at the fracture site has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…E xtensor tendon entrapment at the fracture site is one of the complications in volarly displaced distal radius fracture known as Smith-type fracture or Goyrand-type fracture 7,8 The most commonly associated AO Foundation and Orthopaedic Trauma Association fracture pattern with tendon entrapment is reported to be complete articular radial fractures (2R3C; 69%) 1 . There are reports on entrapments of EPL, EIP, and EDC tendons, of which the EPL tendon is the most frequently involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is emerging evidence suggesting that CT imaging is a reasonable alternative to ultrasound and MRI for soft-tissue injuries. 1,[5][6][7][8] Several studies have demonstrated the utility of CT in visualizing lower extremity tendons as well as diagnosing tendon entrapment and rupture in complex fractures of the ankle and hindfoot. 7,8 In the forearm and hand, Sunagawa et al 5,6 demonstrated that 3D CT imaging can accurately identify flexor tendon rupture of the hand and wrist, locate tendon stumps, and evaluate extensor tendons proximal to the metacarpophalangeal joint.…”
Section: Np4mentioning
confidence: 99%
“…However, such reports are few in number. [1][2][3][4] To our knowledge, there are no case reports of flexor tendon entrapment as a result of carpal fracture-dislocation.…”
Section: Introductionmentioning
confidence: 99%